THE ROLE OF SOCIOLOGY TEACHERSâ TO IMPROVE SOCIAL INTERACTION FOR DISABILITY STUDENT AT REFORMATORY BINA NETRA TUAH SAKATO SUB DISTRICT OF KALUMBUK DISTRICT OF KURANJI PADANG TOWN. - Nasrul, Diary Akhita; Nurdin, Buchari; Rahmad, Darmairal (Pendidikan Sosiologi, 2014)
This research aim to describe the role of sociology teachersâ to improve social interaction for disability student with planning of learning, implementation of study, and evaluation by sociology. This research type is qualitative by using technique of purposive sampling. Type of data used primary data and secondary data. Methods of data collection is done in three ways of that is exploiting of document, interview and observation. Analysis of the data used by the model of interactive data analysis Milles and Huberman with four stages, (1) data collection, (2) data reduction, (3) data displayÂ and (4) data conclusion. This research is concluded that sociology teachersâ to improve social interaction for Â disability student (blind), such as teacher is directed in group student activity and mobility oriented.